A prospective audit of adherence to safe sleeping guidelines in a general paediatric ward and special care nursery. (May 2016) - Griffin, Josh; Heald, Alicia; Davidson, Lucy; Kent, Alison L
Abstract : Aim: Sudden Infant Death Syndrome (SIDS) remains one of the largest causes of infant mortality worldwide, and despite widespread educational campaigns compliance to safe sleeping guidelines remains low in many areas. Hospital staff play a significant role in educating parents on safe sleeping recommendations and providing appropriate sleeping environments for infants. The aim of the study was to evaluate adherence to safe sleeping guidelines in a special care nursery (SCN) and general paediatric ward (GPW). Methods: A prospective audit of sleeping environments in a SCN and GPW with data collected on 10 safe sleeping compliance rules, based on national and international guidelines. Results: Two hundred eleven sleeping environments were observed (161 in SCN, 50 in GPW). Supine sleeping compliance was high in both wards (83% SCN, 82% GPW). Overall the median compliance score was significantly lower in the GPW (7, IQR = 6–7) compared to the SCN (8, IQR = 7–9) (Mann Whitney U test, P < 0.001). Lowest compliance rates were seen in respect to removing soft items from the crib and infant positioning within the crib. Conclusions: Compliance with supine sleeping was high; however, nurses and parents may not be aware, or do not implement, the full suite of safe sleeping guidelines. Further research is required to determine specific reasons for poor compliance and on the effectiveness of educational programmes in improving hospital infant sleeping environments.